Blasting Vibration Characteristics Calculation Formula considering Cylindrical Charge Delay Time. (17th January 2022) - Yang, En; Wang, Zhong-Qi; Xu, Qian
Abstract : The surrounding rock is divided into the elastic zone and the plastic zone according to the motion and deformation characteristics of the medium in rock blasting. The vibration caused by the cylindrical charge blasting is outlined on the basis of previous research concerning the blasting elastic-plastic theory. Meanwhile, a superposition model is used to calculate the vibration of cylindrical charge blasting on the premise of considering the influence of detonation velocity, the number of drug columns, and the time delay between holes. The analysis results show that the blasting causes the uneven spatial distribution of vibration, containing both strong and weak directions. The velocity of the vibration along weak directions decreases slowly with the increase of distance. But generally, the velocity along weak directions is faster. The vibration distribution of a cylindrical charge is closely related to the detonator location. Furthermore, more vibration distributes towards the forward direction of the detonation wave.